COVID-19 pandemic and derogation to human rights - Lebret, Audrey (J Law Biosci, 2020)
Under international human rights law, States can limit the exercise of most human rights if it is necessary to protect the rights of others or collective interests. The exceptional circumstances brought by the COVID-19 global pandemic lead to more extensive, on both their scope and their duration, restrictions of human rights than in usual times. This article introduces the States’ specific right to derogate to human rights in circumstances of public emergency and the conditions of a legitimate derogation in the context of COVID-19. It argues that States must ensure that the general measures they adopt to face the crisis do not disproportionally harm vulnerable people.